Kompetensi dan Peran Partisipasi Masyarakat dalam Mewujudkan Akuntabilitas Pengelolaan Dana Desa - Luh Komang Merawati; Ni Kadek Hariani; Ida Ayu Nyoman Yuliastuti (Politeknik Keuangan Negara STAN, 2022)
This study aims to examine and obtain empirical evidence the effect of village apparatus competency, head village leadership, community participation, utilization of informaton technology and internal control system in accountability of village fund management. The population in this study were 8 villages in Kecamatan Selat, Kabupaten Karangasem, using purposive sampling method, a sample of 44 respondents was obtained consist of the village secretary, head of planning affairs, head of financial affairs, head of BPD, chair of LPM, and head of PKK. The research methodology used is quantitative using multiple linear regression analysis. The results of this study indicate that the variable village apparatus competency, head village leadership, and utilization of information technology have no significant effect on accountability of village fund management, community participation has positive effect on accountability of village fund management, while internal control system has negative effect on accountability of village fund management.